Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2334/josnusd.53.213
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of p53 and PCNA in ameloblastoma and adenomatoid odontogenic tumor

Abstract: Although ameloblastoma and adenomatoid odontogenic tumor (AOT) belong to the same group according to the World Health Organization, they show different biologic behaviors. PCNA, an amplifier of cell proliferation, and p53, a tumor suppressor protein, are overexpressed in some odontogenic lesions. The purpose of this study was to immunohistochemically evaluate the expression of p53 and PCNA to clarify the possible role of these proteins in different behaviors of ameloblastoma and AOT. The immunohistochemical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
2
12
0
1
Order By: Relevance
“…AOT demonstrates a similar level of PCNA immunoreaction to ameloblastomas but exhibits weaker expressions of p53 and MDM2. This implies that AOT has less aggressive behavior than ameloblastomas 86,87. In AOTs, some epithelial tumor cells show a strong cytoplasmic reaction to β-catenin,88 possess whirling epithelial cells expressing cyclin D1, and have spindle-shaped tumor cells that are positive for podoplanin 89.…”
Section: Adenomatoid Odontogenic Tumormentioning
confidence: 99%
“…AOT demonstrates a similar level of PCNA immunoreaction to ameloblastomas but exhibits weaker expressions of p53 and MDM2. This implies that AOT has less aggressive behavior than ameloblastomas 86,87. In AOTs, some epithelial tumor cells show a strong cytoplasmic reaction to β-catenin,88 possess whirling epithelial cells expressing cyclin D1, and have spindle-shaped tumor cells that are positive for podoplanin 89.…”
Section: Adenomatoid Odontogenic Tumormentioning
confidence: 99%
“…Funaoka et al found higher PCNA labeling index for follicular AB than that of plexiform ameloblastoma. Ueno et al, (1989) and Reichart et al, (1995) also stated that the high expression of PCNA in follicular AB can explain its increased potential of recurrence, but Salehinejad et al, (2011) found the highest mean Index of positivity for PCNA in acanthomatous AB. [14] The possibility of malignant transformation in recurrent cases of AB can be determined by PCNA values.…”
Section: Ameloblastin and Other Enamel Matrix Proteinsmentioning
confidence: 99%
“…Ueno et al, (1989) and Reichart et al, (1995) also stated that the high expression of PCNA in follicular AB can explain its increased potential of recurrence, but Salehinejad et al, (2011) found the highest mean Index of positivity for PCNA in acanthomatous AB. [14] The possibility of malignant transformation in recurrent cases of AB can be determined by PCNA values. There was an increase in the expression from UA to follicular AB to plexiform AB and with maximum positivity seen in ameloblastic carcinoma, which may be correlated with biological behavior of the tumor.…”
Section: Ameloblastin and Other Enamel Matrix Proteinsmentioning
confidence: 99%
“…Inflammatory processes are known to increase the risk of cancer development supporting the fact that p53 is a possible Bconnecting pointb etween hypoxia, inflammation, and carcinogenesis [11]. Genetic alterations of p53 have been found in oral squamous cell carcinoma and odontogenic tumors as well as in some osteoblastomas and osteosarcomas, indicating a role in oral tumorigenesis [12,13]. Other authors have shown that p53 is an important factor in oral malodorous-induced apoptosis in periodontal tissues [14].…”
Section: Introductionmentioning
confidence: 96%